An Update on the Changing Indications for Androgen Deprivation Therapy for Prostate Cancer - Kristene Myklak; Shandra Wilson (Prostate Cancer)
Quality of life has become increasingly more important for men diagnosed with prostate cancer. In light of this and the recognized risks of androgen deprivation therapy (ADT), the guidelines and use of ADT have changed significantly over the last few years. This paper reviews the current recommendations and the future perspectives regarding ADT. The benefits of ADT are evident neoadjuvantly and adjuvantly in patients treated with external beam radiation therapy for intermediate- and high-risk disease, in patients who have undergone prostatectomy with lymph node involvement, in high-risk patients after definitive therapy, and in patients who have developed progression or metastasis. Finally, this paper reviews the risks and benefits of each of these scenarios and the risks of androgen deprivation in general, and it delineates the areas where ADT was previously recommended, but where evidence is lacking for its additional benefit.